Neurological Manifestations of Childhood Dengue Fever- Experience in a tertiary care center - Kundu, Gopen Kumar; Talukdar, Manik Kumar; Habiba, Umme; Moni, Umme Kulsum; Ferdosh, Taslima; Das, Konica (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: Dengue fever is a important mosquito-borne illness prevalent in tropical and subtropical regions, posing serious health risks, especially to children. While the common clinical features of dengue, such as high fever, rash, and joint pain, are well-documented, less is known about its neurological manifestations in pediatric patients. These can include a range of symptoms from headaches and seizures to more severe conditions like encephalitis and neuropathy. The complexity of these neurological symptoms often complicates the diagnosis and management of dengue in children.The aim of the study was to evaluate the neurological manifestations of childhood dengue fever and to enhance understanding of the frequency and types of these complications. Methodology: This observational cross sectional study was conducted in the Dengue unit of the Department of Paediatrics and the Department of Paediatric Neurology at BMU from June 2023 to May 2024. Children age 1 month to 15 years who diagnosed with dengue fever (Dengue NS1 positive) were included in this study, while children had large ascites were excluded. After admission to the dengue unit, each child was assessed clinically through a detailed history and thorough physical examination. All children were also evaluated neurologically Results: The data suggests that most children aged 5-10 years (61-120 months) 39(40.63%) with a mean age 96.38 ± 52.45 months, particularly males 56(58.3%), residing in urban areas 71(74.0%), and belonging to the middle social class 77(80.2%), may be at higher risk for dengue fever. Fever had 96(100.0%) of subjects, anorexia and vomiting 74(77.1%), and pain 60(62.5%) respectively. More than one fourth (28.1%) subjects had headache followed by encephalopathy 3(3.1%), febrile seizures 2(2.1%), and encephalitis-like features such as lethargy, confusion and coma 2(2.1%) respectively. Conclusion: Fever remains the most common presenting feature of dengue in children; however, a notable proportion develop neurological manifestations, including headache, encephalopathy, febrile seizures, and encephalitis-like features. Early recognition of these complications is essential for appropriate management and improved outcomes. J Bangladesh Coll Phys Surg 2026; 44: 111-116